2022
DOI: 10.1097/qai.0000000000003109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on HIV Testing Among AIDS Institute–Funded Providers in New York State–A Time Series Analysis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The number of HIV tests reported by NYSDOH AIDS Institute-funded providers decreased by more than 50% in NYS from March 2020 through June 2021. 31 Similarly, the number of HIV tests reported nationally was substantially lower in 2020 than in 2019. 30 This study is subject to at least 2 limitations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of HIV tests reported by NYSDOH AIDS Institute-funded providers decreased by more than 50% in NYS from March 2020 through June 2021. 31 Similarly, the number of HIV tests reported nationally was substantially lower in 2020 than in 2019. 30 This study is subject to at least 2 limitations.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the percentage of Behavioral Risk Factor Surveillance System (BRFSS) participants from NYS who reported HIV testing during the year deceased markedly from 2019 (17.3%) to 2020 (12.5%), translating to more than 300 000 fewer HIV tests (Rakkoo Chung, PhD, e-mail communication, November 2021). The number of HIV tests reported by NYSDOH AIDS Institute–funded providers decreased by more than 50% in NYS from March 2020 through June 2021 31. Similarly, the number of HIV tests reported nationally was substantially lower in 2020 than in 2019 30…”
Section: Discussionmentioning
confidence: 99%
“…Our work provides additional context around the existing literature on changes in PrEP use and STIs/HIV during the COVID-19 pandemic. Multiple studies have demonstrated decreases, sometimes transitory, in PrEP use and STI/HIV testing; 2–6,20 however, it was not always clear whether these decreases were associated with reduced sexual activity. Furthermore, data suggest an increase in STIs as social activity has reopened.…”
Section: Discussionmentioning
confidence: 99%
“…1 At the individual level, people may have changed their sexual behavior as part of reducing COVID-19 exposure. 2 The pandemic resulted in decreases in use of STI/HIV prevention tools, such as HIV pre-exposure prophylaxis and routine testing, [2][3][4][5][6] and in reduction of sexual practices themselves. 2,3,7 Since the removal of nearly all COVID-19 mitigations, the nation has seen an increase in STI testing and diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation